Entrepreneurship Management Education as a Catalyst for Student Interest in Developing Social Entrepreneurship at Pelita Bangsa University - Abdurahman, Fairuz Rifqi; Hendrayati, Heny; Suryana, Suryana; Mulyadi, Hari; Harisandi, Prasetyo; Yusriani, Sri (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study aims to analyse the influence of entrepreneurship management education on students’ interest in developing social entrepreneurship. The primary focus lies on the contribution of business planning, social leadership, and impact management to students’ social entrepreneurship orientation. Method: A quantitative approach with a survey method was used to collect data from 169 active students of the Entrepreneurship Study Program, Faculty of Economics and Business, Pelita Bangsa University, who have taken at least one Entrepreneurship Management course. A purposive sampling technique was used in the selection of respondents. Results: The analysis shows that entrepreneurship management education significantly and positively affects students’ interest in developing social entrepreneurship (p-value = 0.000, t-statistic = 13.326, path coefficient = 0.572). This finding confirms that the managerial approach in entrepreneurship learning effectively improves students’ knowledge, skills, and entrepreneurial spirit oriented towards social values.. Novelty: The novelty of this study lies in the specific focus on entrepreneurial management education, which is different from general entrepreneurship education, with a managerial process approach. The practical implication is that the results can serve as a basis for curriculum designers and higher education policy makers to strategically integrate social entrepreneurship modules to foster sustainable social innovation among the younger generation.